Teaching Question Words For Adult Leaners By Using The Pictures Of Giant Buildings As A Teaching Media - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
AbstractThis study aims to investigate and improve the learners' mistakes in applying question words; what, when, where, why, who, whose, whont, which and how through the pictures of a gient buildings. Most new leaners expect to spcak the languagc they learrh as soon as they can, without thinking over about thc langauge grammar, particularly in applying those question words. Teachers can, of course, conduct many distingusih teaching tools in order to improve the learners progress in learning a langauge. Mistakes normanlly takes place when people learn a language let alonc when they try to speak. Adult learners sometimes misused questions words, espccially What, Where, When due to having misleading about QW. The researcher found out that by using the pictures of giant buildings, as a teaching media. Ile strongly believes that the picture of giant building can minimize the mistakes and improve their speaking skills in terms of using question words. Question words are used to ask about specific qualities, times, places, people, etc. When the researcher traveled to some big cities in the world hc found that some people asked about those huge building. Perhaps they have never seen such a tall buildings in their cities. The questions that the researcher found such as; Hmv is this huilding?. How many levels are they?. Who huilt this building?. What are this building for?.When HYlN this building built?. Who designed it? This is the very rcason why the researcher is interestcd in conducting this study, besides, the learners feel fun and enjoy learning. lt is expected that this study can be significant for those learners in mastering English. Keywords-Question words; pictures of giant buildings; aduk learners; speaking skills